475. Describing the impact of the COVID-19 pandemic on HIV care in Latin America. (31st December 2020) - Person, Anna K; Maruri, Fernanda; Brazier, Ellen; Madero, Juan G Sierra; Rouzier, Vanessa; Carriquiry, Gabriela; Avelino-Silva, Vivian I; de Alencastro, Paulo Ricardo; Ikeda, Maria Leticia R; Souza, Rosa Alencar; Rocha, Simone Queiroz; Cesar, Carina; et al.
Abstract: Background: The effects of the COVID-19 pandemic on people living with HIV (PWH) are unknown. Beyond SARS-CoV-2 co-infection, the pandemic may have devastating consequences for HIV care delivery. Understanding these is crucial as reduced antiretroviral therapy (ART) availability alone could lead to ≥500, 000 AIDS-related deaths in 2020–2021. With Latin America now a focal point in the pandemic, we sought to describe the impact of COVID-19 on HIV care at Latin American clinical sites. Methods: Caribbean, Central and South America network for HIV epidemiology (CCASAnet) and additional Brazilian HIV care sites in Argentina, Brazil, Chile, Haiti, Honduras, Mexico, and Peru were included. An electronic survey of COVID-19 effects on HIV clinic operations was administered in Spanish or English via phone and email, April 28-June 2, 2020. We also compared national COVID-19 case, mortality, and policy data from public sources. Results: Brazil's and Mexico's epidemics appear most pronounced, with >10, 000 confirmed COVID-19-related deaths (Figure 1); countries implemented "social distancing" policies at different times after initial cases, with Haiti earliest and Mexico latest (Figure 2). Nearly all 13 sites reported decreased hours and providers for HIV care. Twelve of 13 reported increased use of telehealth, suspension/postponements of routine HIV appointments, and/or suspension of HIV research. Eleven of 13 reported initiation of new COVID-19 research but suspension of community HIV testing, and nearly half provided additional ART supplies. Nearly 70% reported impacts on HIV viral load testing and nearly 40% reported personal protective equipment stock-outs (Table). All 13 sites experienced changes in resources/services in tandem with national policies; there was wide variation, however, in the number of economic and health supports implemented thus far (e.g., quarantines, tax deferrals, interest rate reductions, etc.), from 172 COVID-19-related policies in Brazil to only 30 in Mexico. Table Site Assessment of Impacts of the COVID-19 Pandemic on HIV services in Latin America at CCASAnet and Coorte Sites, N=13 Figure 1. Cumulative mortality due to COVID-19 in countries within which CCASAnet and Coorte sites are located Figure 1 footnote: Source for mortality counts: the WHO COVID-19 Dashboard, available at: https://covid19.who.int/ All data were up-to-date as of, and were accessed on, June 17th, 2020 Figure 2. Cumulative cases of COVID-19 in countries within which CCASAnet and Coorte sites are located and dates (relative to the day on which the first positive case of COVID-19 was detected) of general social distancing, public health emergency, or mass quarantine policy introduction (vertical dashed lines), 2020 Figure 2 footnote: Source for case counts: the WHO COVID-19 Dashboard, available at: https://covid19.who.int/ Source for health policy implementation: the United Nations Economic Council for Latin America & the Caribbean, available at: https://cepalstat-prod.cepal.org/forms/covid-countrysheet/index.html All data were up-to-date as of, and were accessed on, June 17th, 2020 Conclusion: The COVID-19 pandemic has already had a substantial effect on daily operations of HIV clinics in Latin America. The downstream effects of these impacts on HIV outcomes in Latin America will need to be further studied. Disclosures: All Authors : No reported disclosures